Relationship of Nitrate and Phosphate Content with Phytoplankton Abundance at the West Kambang River Estuary, Lengayang District, Pesisir Selatan, West Sumatra - Fatma, Nisa Tria; Nedi, Syahril; Nurrachmi, Irvina (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2022)
This research was conducted in February 2021 in the Estuary of the West Kambang River, Lengayang District, Pesisir Selatan, West Sumatra. This study aims to analyze the relationship between nitrate and phosphate concentrations with the abundance of phytoplankton in the West Kambang River Estuary. The method used in this study is a survey method. Determination of sampling stations was carried out by purposive sampling based on anthropogenic activities around the Estuary of the West Kambang River. Based on the results of the study, nitrate concentrations ranged from 0,76 ̶ 0,86 mg/L, phosphate concentrations ranged from 0,85 ̶ 0,94 mg/L, the average abundance of phytoplankton ranged from 201,50 ̶ 284,27 ind/L. Based on the one way Anova test, the concentration of nitrate, phosphate and abundance of phytoplankton did not differ significantly between stations. The results of simple linear regression test showed that the concentration of nitrate had a weak relationship with the abundance of phytoplankton and phosphate had a moderate relationship with the abundance of phytoplankton.